Between orientalists and Al Jazeera: image of Arabs in the West (comparative inquiry) - Ramdane, Tahraoui; Souad, Merah (Centre for Promoting Ideas, USA, 2001)
Western writers, designers, and artists turned their attention to study and analyze the cultural, social, intellectual heritage, as well as languages, peoples, history, and politics of the Near-Eastern societies. However, despite academic and referential value of these studies, they largely contributed to the creation of a unique stereotyped personality for the Orient in general and the Arabs in particular. The accuracy and authenticity of that unique personality have never been verified by other sources. Hence, the deep-rooted collective image of the orient in the western mind has been largely relying on the representation which the orientalists provided about Arabs and their culture and history.In fact, despite the basic change in political and economic landscape in the last decades, particularly after the end of the cold war and the lapse of the Soviet polarity, and although we live in an era marked by the explosion of information and globalization, orientalists views on the East continue to be the first consulted source for western intellectuals, policy makers, and media. Indeed, orientalism literature is a key source of reference that is regularly consulted by the Arabs themselves and intelligentsia circles in particular, in subjects ranging from the Arab and Islamic history to the problems of Arab identity. However, due to the rise of unforeseen transformational factors in the Arab world in the last decade, mainly in communication and mass media, such as the Arab media recent liberality, the establishment of various Arabic television broadcasting channels, chiefly the renowned Al-Jazeera, the old monopoly of the orientalists seems likely to lose its inherited influence. The local new sources of information and analysis are increasingly offering a more genuine image of the Arabs to the West in particular, and the entire world in general. This paper will shed some light on the role of Al-Jazeera channel as one of the most efficient means of communication and dialogue with the West, so as to convey and explain the true image of the Arabs to the Western public opinion. It will also try to measure the success of Al-Jazeera in changing or questioning the credibility of the classic western stereotype about Arabs planted by both, the early Orientalists and western politicians in the minds of people. Furthermore, the paper will analyze the degree of success that Al-Jazeera achieved in helping its Arab viewers to reconstruct their self awareness and interaction with the persistent issues in the Arab world, especially after the long years of official channel and media control over the public, which continued to reproduce an official message that never reflected the reality of life. We are aware of the difference in nature between the two elements of this study; orientalists’ views based on studies, and Al-Jazeera presentation as media. Nevertheless, our prime objective is to address the effects of the endeavors of both, orientalists and Al-Jazeera in the common western memory. We will try to highlight the efforts of Al-Jazeera in changing the impression of western men on Arab’s culture and personality. Our objective is to contribute to the efforts that strive for better understanding between Arabs and their counterparts, and preferable perception towards the affairs of the Arab world, in order to achieve a better communication between two powerful cultures, based on mutual respect.